Daya Antibakteri Fraksi n-butanol Kulit Buah Delima Putih (Granati fructus cortex) terhadap Streptococcus mutans (Antibacterial Activity of White Pomegranate Pericarp (Granati fructus cortex) n-butanol Fraction against Streptococcus mutans) - Gea Akalili abrina; Sukanto .; Niken Probosari (Pustaka Kesehatan, 2015)
Pomegranate white pericarp contains flavonoids, tannins and phenols which are antibacterial. These compounds are soluble in n-butanol fraction. Streptococcus mutans (S. mutans) is normal bacteria of oral that can be pathogenic and cariogenic, so this should be inhibited bacterial growth. This research was aimed to determine whether n-butanol fraction of pomegranate pericarp had antibacterial activity against S. mutans and how much the most effective concentration in inhibiting growth and done in vitro. Possibility of n-butanol fraction pomegranate pericarp could inhibit growth of S. mutans. The method used was a pour plate using a serial dilution methods with a concentration of 0,313% up to 10%. Kruskal Wallis and Mann Whitney test showed significant difference between groups with p=0.000 (p< 0.05). In conclusion, namely n-butanol fraction of pomegranate pericarp had antibacterial activity against S. mutans and the most effective concentration of the antibacterial concentration was 10%. Suggestions for further research for role of compounds in pomegranate pericarp that inhibit the growth of S. mutans. Keywords: n-butanol fraction, S. mutans, White pomegranate pericarp